2008
DOI: 10.1001/archsurg.2007.73
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gene Expression Profiles in Cells of Peripheral Blood to Identify New Molecular Markers of Acute Pancreatitis

Abstract: Microarray analysis in transcriptional profiling of PBMCs showed that genes that are uniquely related to molecular and pancreatic function display differential expression in acute pancreatitis. Profiling genes obtained from an easily accessible source during severe pancreatitis may identify surrogate markers for disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…Therefore, selective induction of PLD1 by pathogen activation might play a relevant role in the late phase of immune response and in chronic inflammation. Microarray analysis during the transcriptional profiling of peripheral blood mononuclear cells associated with acute pancreatitis demonstrated that PLD1 was the top up-regulated gene (61), suggesting that it is a suitable molecular marker of acute pancreatitis. Genetic silencing of PLD1 effectively blocked the cytokine/chemokine production, vascular permeability, and leukocyte recruitment triggered by tumor necrosis factor ␣ (TNF␣) in an in vivo peritonitis model (62).…”
Section: Selective Induction Of Pld1 By Inflammatory Cytokinesmentioning
confidence: 99%
“…Therefore, selective induction of PLD1 by pathogen activation might play a relevant role in the late phase of immune response and in chronic inflammation. Microarray analysis during the transcriptional profiling of peripheral blood mononuclear cells associated with acute pancreatitis demonstrated that PLD1 was the top up-regulated gene (61), suggesting that it is a suitable molecular marker of acute pancreatitis. Genetic silencing of PLD1 effectively blocked the cytokine/chemokine production, vascular permeability, and leukocyte recruitment triggered by tumor necrosis factor ␣ (TNF␣) in an in vivo peritonitis model (62).…”
Section: Selective Induction Of Pld1 By Inflammatory Cytokinesmentioning
confidence: 99%
“…Moreover, microarray analysis in the transcriptional profiling of peripheral blood mononuclear cells during acute pancreatitis showed that PLD1 is the top upregulated gene (14). However, the functional role of PLD in a pathological lesion of chronic inflammatory diseases, such as RA, remains unknown.…”
mentioning
confidence: 99%
“…It has been suggested that tumors could be recognized by the immune system and that cancer cells can evade the elimination of immunological surveillance [6]. Therefore, immune evasion might occur as an early event in tumorigenesis [7], [8]. Peripheral blood mononucleated cells (PBMCs) mainly consist of monocytes, T cells, B cells, granulocytes, and natural killer cells [9] and act as the first line of defense against malignancy in the immune system [9].…”
Section: Introductionmentioning
confidence: 99%